Aeroelastic characteristics on deformed high aspect ratio wing with various tip deflections - Rosly, Nur Asyikin (2019)
A high aspect ratio (HAR) wing model that exhibits geometric nonlinearities has been analysed to observe its impact in terms of static and dynamic characteristics. The research work was motivated by the lack of study from past researchers towards the modal properties of the HAR wing model using experimental modal analysis (EMA) in undeformed and deformed configurations. The undeformed configuration refers to exclusion of gravitational loading effect while deformed configuration considers the gravitational effect in bending direction. A number of tip store models was also considered in order to represent various degree of bending deformations, which is quantified in terms of tip deflection. To idealize an experimental model of HAR wing, the parametric sizing was conducted by considering the size of the wind tunnel test section, as well as its maximum speed with both undeformed and deformed configurations were taken into account. The final wing dimension was then chosen to be of 800mm×50mm×1.25mm along with three various tip store diameter of 10mm, 12mm, and 14mm. Following this, the wing model was fabricated to enable the EMA testing, ground static testing, and wind tunnel flutter testing to be conducted. In terms of EMA testing, the findings confirmed that the chordwise-bending and torsion modes for the undeformed configuration changes to chordwise-torsion and torsion-chordwise modes respectively when the wing was in the deformed configuration. The natural frequency for both chordwise-torsion and torsion-chordwise modes decreases as the tip deflection increases, with the chordwise-torsion mode occurs at a much lower frequency than the torsion-chordwise mode. This clearly shows that wing in undeformed and deformed configuration have different modal characteristics and behave differently. Following this, the model updating was employed to bring the FE model closer to its experimental counterpart, where the discrepancies in terms of the first seven natural frequencies were minimized from 44% to be about 10% with the magnitude of frequencies difference is lesser than 1.5Hz. In addition, good agreement in mode shapes were also acquired in terms of modal assurance criterion (MAC) with no occurrence in mode shape swap between the experimental and FE models. The updated FE model was further validated against the ground static testing for an incremental tip force on the wing model and the result provides a good agreement between them in terms of tip deflection. Following this, the wind tunnel flutter testing envelope was idealised and the updated FE model has successfully predicted the flutter speed of undeformed wing configuration whereby the percentage of differences is not more than 10%. Since there is still no commercially available software for flutter prediction of deformed wing configuration; hence, the available validated numerical solution along with its corresponding experimental results may provide a certain degree of insight in understanding its flutter characteristics. Based on the finding, the flutter speed may unnecessarily decrease when the tip deflection increase although reduction in chordwise-torsional mode frequency led to a reduction in the frequency gap between the flutter modes. Hence, it is concluded that the flutter speed of the deformed HAR wing only reduces until a certain degree of tip deflection and beyond this point the flutter speed begins to increase.